Migraine and Cranial Autonomic Symptoms in Children and Adolescents: A Clinical Study. (February 2015) - Raieli, V.; Giordano, G.; Spitaleri, C.; Consolo, F.; Buffa, D.; Santangelo, G.; Savettieri, G.; Vanadia, F.; D'Amelio, M.
The frequency of cranial autonomic symptoms in children affected by primary headaches is uncertain. The aim of our study was to estimate the frequency of symptoms in pediatric headaches and correlate it with main migraine characteristics. A questionnaire investigating the presence of cranial autonomic symptoms was administered to all children with primary headache for 2 years. A total of 230 children with primary headache (105 males, 125 females) were included. Two hundred two children were affected by migraine and 28 (12.2%) by other primary headaches. Cranial autonomic symptoms were significantly complained by migraineurs (55% vs 17.8%) ( P < .001) and by children with higher frequency of migraine attacks (odds ratio = 2.6, confidence interval = 1.4-4.7, P = .001). Our findings show that cranial autonomic symptoms are rather common during pediatric migraine attacks. The association between cranial autonomic symptoms and higher frequency of attacks might suggest the role of the trigeminal-autonomic reflex in migraine pathophysiology.